2016
DOI: 10.1007/s11250-016-1006-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E supplementation of undernourished ewes pre- and post-lambing reduces weight loss of ewes and increases weight of lambs

Abstract: The aim of this study was to test if vitamin E supplementation during late gestation and early lactation would affect the weight of ewes under nutritional restriction and the performance of their lambs. Mature Rambouillet ewes (n = 37) were fed a diet that supplied 70 % of the energy and 80 % of recommended protein requirements and randomly assigned to either vitamin E (vit E, n = 20, 4 IU of α-tocopherol kg(-1) of live weight) or control (n = 17, without vitamin E supplementation). During the experimental per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
4
7
2
Order By: Relevance
“…It is perhaps important to note that the birth weight reported in the present study was below values previously reported for this breed, at either a similar location [33] or elsewhere [34,35]. This outcome could be attributed to the amount of diet offered which, for all three treatments, did not meet the NRC [28] requirements-the Control diet provided too little energy and both of the Opuntia treatments provided too little protein or energy.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…It is perhaps important to note that the birth weight reported in the present study was below values previously reported for this breed, at either a similar location [33] or elsewhere [34,35]. This outcome could be attributed to the amount of diet offered which, for all three treatments, did not meet the NRC [28] requirements-the Control diet provided too little energy and both of the Opuntia treatments provided too little protein or energy.…”
Section: Discussioncontrasting
confidence: 80%
“…Unfortunately, technical issues prevented us from analyzing milk composition, so this question awaits future studies. Previous studies have demonstrated that the growth performance of lambs is highly related to birth weight, so individuals that are heavier at birth grow faster and are heavier at weaning [30,33,52]. However, in the present study, growth rate was not related to birth weight perhaps because the birth weights were low, as discussed above.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This is an important stage not only for animal welfare reasons, but also from a production standpoint as weanlings that maintain their growth rates through the weaning process are healthier and heavier by slaughter [23]. Benefits from nutritional supplements may help weaned animals and poultry increase body size as well [24]. Nanoparticles engineered for nutrient delivery could facilitate this supplementation and bolster growth rates of livestock by increasing nutrient cargo bioavailability.…”
Section: Nutrient Deliverymentioning
confidence: 99%
“…As tocopherol levels were demonstrated to impact important pregnancy outcomes, and levels are directly impacted by diets high in processed foods, as those often found in the US, but less prevalent in developing countries, evaluation of tocopherol status in pregnant women and their infants in these two different cultures has the potential to inform development of dietary intervention to help optimize diets in pregnancy and positively impact maternal and infant outcomes. Evidence that tocopherol levels, particularly α-tocopherol, are associated with pregnancy outcomes, such as fetal growth, is well documented [ 16 , 17 , 18 , 19 ]. Therefore, comparing plasma tocopherol levels with selected pregnancy outcomes such as length of gestation, development of preeclampsia, fetal growth, pregnancy loss, and other maternal and fetal factors between United States and Nigerian maternal–infant populations could illuminate the need for nutritional interventions to positively impact adverse pregnancy outcomes in high-risk populations.…”
Section: Introductionmentioning
confidence: 99%